A livelihood in a risky environment: farmers’ preferences for irrigation with wastewater in Hyderabad, India - Saldias, C.; Speelman, S.; Drechsel, Pay; Huylenbroeck, G. van (Springer, 2017)
Most cities in developing countries fail to treat their wastewater comprehensively. Consequently, farmers downstream use poor-quality water for irrigation. This practice implies risks for farmers, consumers and the environment. Conversely, this water supply supports the livelihood of these farmers and other stakeholders along the value chains. Linking safer options for wastewater management with irrigation could therefore be a win–win solution: removing the risks for society and maintaining the bene ts for farmers. However, in developing countries, the high investment costs for the required treatment are problematic and the willingness of farmers to pay for the water (cost recovery) is often questionable. Using a choice experiment, this paper gives insight into farmers’ preferences for wastewater use scenarios, quantifying their willingness to pay. The case study is Hyderabad, India. Farmers there prefer water treatment and are prepared to pay a surplus for this. Considering the costrecovery challenge, this information could be valuable for planning small on site wastewater treatment systems.